Economic role of the Roman army in province of Lower Moesia (Moesia Inferior) - Duch, Michał (Instytut Kultury Europejskiej UAM, 2017)
This books takes a comprehensive look at the Roman army as a factor which prompted substantial changes and economic transformations in the province of Lower Moesia, discussing its impact on the development of particular branches of the economy. The volume comprises five chapters. Chapter One, entitled “Before Lower Moesia: A Political and Economic Outline” constitutes an introduction which presents the economic circumstances in the region prior to Roman conquest. In Chapter Two, entitled “Garrison of the Lower Moesia and the Scale of Militarization”, the author estimates the size of the garrison in the province and analyzes the influence that the military presence had on the demography of Lower Moesia. The following chapter – “Monetization” – is concerned with the financial standing of the Roman soldiery and their contribution to the monetization of the province. Chapter Four, “Construction”, addresses construction undertakings on which the army embarked and the outcomes it produced, such as urbanization of the province, sustained security and order (as envisaged by the Romans), expansion of the economic market and exploitation of the province’s natural resources. In the final chapter, entitled “Military Logistics and the Local Market”, the narrative focuses on selected aspects of agriculture, crafts and, to a slightly lesser extent, on trade and services. The book demonstrates how the Roman army, seeking to meet its provisioning needs, participated in and contributed to the functioning of these industries.